Tensile and erosion behaviour of medium calcined alumina microparticles on GFRP composites fabricated with vacuum bagging process. (2021) - Bharath, D.; Sandhya Rani, B.; Saritha, V.; Irshad Khan, P.; Kumar Chokka, Syam
Abstract: Fiber-reinforced polymer matrix composites have high specific stiffness and high strength to weight ratio draw the attention of researchers to enhance the properties of the composite with a reduced cost. The performance of the composites is being affected by fiber volume fraction and microparticulate reinforcement. Fiber volume fraction can be controlled with vacuum pressure. A medium calcined alumina micro particulates (Al2 O3 ) was considered as a 3% weight percentage of the matrix at random. The particles were distributed using mechanical stirrer and spraying machines. The parametric effect was studied using tensile test data and erosion wear test data. From the results, it was observed that the particulate addition may increase the erosion resistance of the composite.